2008
DOI: 10.1038/gt.2008.72
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy progress and prospects cancer: oncolytic viruses

Abstract: The past 2 years have seen several major advances in oncolytic virotherapy. Studies on the interaction between viruses, immune responses and tumor microenvironment have provided important insight, while clinical trials have shown promise. This review summarizes key findings in this field over the past 2 years, and provides directions for future success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
126
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 60 publications
1
126
0
3
Order By: Relevance
“…Previous reports have shown the therapeutic potentials in other tumors. In clinic, a multicenter randomized phase 3 clinical trial showed that the combination therapy with H101 for head and neck squamous cell carcinoma and esophageal cancer yielded a 27% increase in overall response rates compared with fluorouracil plus cisplatin-based chemotherapy alone (22). This virus was approved by the Chinese State Food and Drug Administration for the treatment of late-stage refractory nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown the therapeutic potentials in other tumors. In clinic, a multicenter randomized phase 3 clinical trial showed that the combination therapy with H101 for head and neck squamous cell carcinoma and esophageal cancer yielded a 27% increase in overall response rates compared with fluorouracil plus cisplatin-based chemotherapy alone (22). This virus was approved by the Chinese State Food and Drug Administration for the treatment of late-stage refractory nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of viruses have shown oncolytic properties including adenovirus, herpes simplex virus, Newcastle disease virus, vesicular stomatitis virus and reovirus (22). Among a variety of oncolytic viral agents, CRAds specifically aimed at killing tumor cells while sparing normal cells have been developed as new agents for cancer therapy (23,24), and demonstrated efficacy and safety in preclinical (25,26) and clinical trials (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic viruses displaying various mechanisms of action have been developed over the past 15 years. These include viral mutants, in which genes critical for viral growth in normal cells but not in tumor cells were deleted, pseudotyped viruses, in which normal viral tropism was ablated, and engineered viruses binding to specific surface receptors that are expressed exclusively/preferentially on tumor cells (Alemany et al, 2000;Khuri et al, 2000;Kirn, 2000;Fukuhara et al, 2005Fukuhara et al, , 2009Kasuya et al, 2005;Liu and Kirn, 2008;Dorer and Nettelbeck, 2009). Interestingly, oncolytic viruses can kill apoptosis-resistant tumor cells, and do not show cross-resistance with existing therapies.…”
Section: Strategies To Selectively Kill Tumor Cellsmentioning
confidence: 99%
“…5,6 However, limited therapeutic effect has been reported and further development of Onyx-015 was abandoned in the United States. 7 The rights of Onyx-015 were bought by a Chinese company, Sunway Biotech, which has completed phase III clinical studies with H101, an Ad structurally similar to Onyx-015. 2 The company reported a 79% positive response rate for H101 plus chemotherapy as compared with 40% for chemotherapy alone in clinical trials performed on Chinese cancer patients.…”
Section: Introductionmentioning
confidence: 99%